The influence of vertical jump ability on spike jump height with an approach run in female volleyball players - Kinomura, Y.; Nishimura, S.; Kataoka, H.; Iida, S. (Serbian Journal of Sports Sciences, 2021)
This study aimed to investigate the relationship between spike jump (SPJ) height and countermovement jump (CMJ) height or index of a repeated rebound jump (RJ) in female college volleyball players. Twenty-two college female volleyball players were asked to perform CMJ, RJ, and an SPJ with a 3-step running approach. After collecting the data, correlations between SPJ height and CMJ height or RJ-index were investigated. There were significant correlations between SPJ height and CMJ height or RJ-index for all participants. Moreover, when participants were classified into upper or lower groups according to SPJ height, both CMJ height and RJ-index of the upper group were significantly larger than those of the lower group. These results suggest that the lower group needs to increase their CMJ height and RJ-index to achieve an SPJ height similar to the upper group. Alternatively, a strong positive correlation between SPJ height and CMJ height was observed in the upper group, which suggests that improving CMJ height is required to increase SPJ height. This implies the importance of strength training that involves extensive flexion and extension of the lower limb, such as squat-jump.